Pentingnya Menjaga Higiene Dan Sanitasi Di Lingkungan The Sahid Rich Hotel Yogyakarta - Emmita Devi Hari Putri (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2013)
The Sahid Rich Jogja is a new hotel in the city of Yogyakarta , standing in 2011 and managed by the Hotel Sahid Group . This hotel is the 27th which is managed by the Sahid Group Indonesia . The founders of this hotel is the native city of Yogyakarta . It is a tribute of the founders of The Rich Sahid Yogyakarta to their home town . The hotel has 9 floors which stands majestically . Still located in the city center , The Rich Sahid Yogyakarta competitor comes into the hotel stands in the city of Yogyakarta . The development of Rich Sahid Yogyakarta itself takes approximately one year . In the tourism industry hotel industry is a sector that is engaged in and is very influential on the development of tourism , which are required to provide the hotel guest satisfaction to both of the facilities provided to meet the needs of guests . Therefore , the hotel should be able to create the atmosphere needed by the guests , one way to improve hygiene and sanitation in all department.Higiene is a business that focuses on preventive health activities to the efforts of individual health , personal health and human effort . Sanitation means business while emphasizing preventive health activities to the business environment of human health. Keyword : Hygiene , Sanitation , Environment